Pengaruh Kurikulum Merdeka Terhadap Pembentukan Karakter di SMP Islam Al-Azhar Cairo Palembang - Nisa, Nurul Hidayahtun; Niswah, Choirun; Ibrahim, Ibrahim (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to determine whether the implementation of the independent curriculum (kurikulum merdeka) has an impact on character development at SMP Islam Al-Azhar Cairo Palembang. The research population consists of 140 seventh-grade students at SMP Islam Al-Azhar Cairo Palembang. The instruments used for data collection are questionnaires and documentation. Data collection took place from April 25 to May 29, 2024. The data analysis technique used is simple linear regression analysis. The research results indicate, first, that there is an impact of the independent curriculum implementation on the character development of students at SMP Islam Al-Azhar Cairo Palembang. This is evidenced by the data analysis results, showing that the calculated r value of 0.712 is greater than the product moment table r value, which is 0.312 at a 5% confidence interval and 0.403 at a 1% confidence interval for N = 40. Second, the implementation of the independent curriculum has a high impact on the character development of students at SMP Islam Al-Azhar Cairo Palembang, as the calculated r value of 0.712 falls within the range of 0.600 to 0.800, indicating a high/strong interpretation